Effectiveness of autologous leukocyte platelet-rich fibrin on orthodontic tooth movement: a split-mouth clinical study - Prahlad Jha; Vaibhav Misra; Rajeshwar Singh; Sonal Attri (International Journal of Research in Medical Sciences, 2026)
Background: Prolonged orthodontic treatment is associated with increased risk of enamel demineralization, root resorption, periodontal complications and reduced patient compliance. Leukocyte platelet-rich fibrin (L-PRF), an autologous platelet concentrate rich in growth factors and cytokines, has been proposed as a biological adjunct to accelerate orthodontic tooth movement. To evaluate the effectiveness of L-PRF in enhancing orthodontic canine retraction. Methods: A split-mouth clinico-experimental study was conducted on nine patients aged 15–25 years requiring bilateral maxillary first premolar extractions. The right side received L-PRF placement in the extraction socket and served as the experimental side, while the left side acted as the control. Canine retraction was performed using nickel-titanium closed-coil springs delivering 150 g force. Tooth movement was assessed using three-dimensional digital models at baseline (T0), one month (T1), two months (T2) and three months (T3). Data were analyzed using paired t-test, repeated measures ANOVA and Bonferroni post-hoc analysis. Results: Greater canine movement was observed on the L-PRF side throughout the study period. Statistically significant acceleration was noted during the initial phase of retraction, whereas differences during later intervals were not significant. Both groups demonstrated significant time-related variations in tooth movement. Conclusions: L-PRF enhanced orthodontic tooth movement primarily during the early stages of canine retraction. It may serve as a safe, minimally invasive and biologically effective adjunct for accelerating orthodontic treatment and potentially reducing overall treatment duration.